Five Years into Democracy - (:unkn) unknown (My University, 2001)
The papers in this volume were first presented in two different tracks ("assessing quality of life and living conditions to guide national policy" and "happiness, life satisfaction and subjective well-being") at the Third Conference of the International Society for Quality of Life Studies, 20-22 July 2000, Girona, Spain. Taken together the papers report in full on the 1999 round of research for the Quality of Life Trends project, the last before the new millennium.
Keywords: African Research